Physiological and genetical aspects of the broad based potato population (Solanum tuberosum L.) in the Netherlands and Northern Finland - Zaban, A; Veteläinen, Merja; Celis-Gamboa, C B; Berloo, R van; Häggman, Hely; Visser, R G F (Suomen maataloustieteellinen seura, 2006)
v ok BEL/SBI